PERENCANAAN DAN PENGENDALIAN OPERASI KEPOLISIAN DALAM MENANGANI UNJUK RASA DI WILAYAH POLRES MOJOKERTO - Zakky, Firnanda Auliya; Soekorini, Noenik; Taufik, Moh. (Gapenas Publisher, 2025)
Demonstrations are a form of public expression guaranteed by Law No. 9 of 1998. However, in practice, they often have the potential to cause disturbances to public security and order if not properly controlled. This study aims to analyze the planning and control of police operations in handling demonstrations in the Mojokerto Police District. The research method used is an empirical juridical approach, with data collection techniques through interviews, observation, and documentation. The results of the study show that the Mojokerto Police carry out operational planning based on the principles of prevention, proportionality, and humanism. Operational control is carried out through the implementation of Standard Operating Procedures (SOPs), cross-sector coordination, and the application of the principle of negotiation before repressive action. The obstacles found include limited personnel resources, infrastructure, and the unpredictable dynamics of the masses. Therefore, strengthening personnel capacity and more effective coordination with relevant parties are strategic steps to optimize police operation control